Discovery of RAR-related Orphan Receptor γt Inverse Agonists - Niemeläinen, Miika (My University, 2021)
BACKGROUND Technological advances have provided modern approaches for drug discovery and development. Its application, computer-aided drug design (CADD), enables solving complex drug design challenges practically unsolvable by traditional methods. Here, CADD was applied for a drug target retinoic acid receptor-related orphan receptor gamma t (RORγt). RORγt is a nuclear receptor that mediates inflammation and is connected to multiple chronic inflammatory diseases. RORγt inhibition proposes anti-inflammatory effects and, as such, RORγt has been identified as an appealing drug target. The highest inhibition is achieved with inverse agonist -inhibitors. Due to unspecificity and complexity of RORγt, no effective drugs targeting RORγt have been developed so far. Accordingly, CADD approach can be justified to address this challenge. UNMET MEDICAL NEED Some patients suffering from inflammatory diseases do not respond sufficiently to the current therapies. Hence, search for novel therapies can be justified, and RORγt inhibition is a promising option for this purpose. AIM OF THE STUDY Modern CADD approaches were executed to discover novel RORγt inverse agonists. MATERIALS AND METHODS Several CADD methods were utilized including ligand- and structure-based drug design. RESULTS 29 novel potential RORγt inverse agonists were discovered. CONCLUSION CADD protocol was demonstrated suitable for discovering novel potential RORγt inverse agonists.
Keywords: RORγt, CADD, inverse agonist